3D bioprinting of hydrogels with embedded cells - Pui, Nigel Min Wei (2017)
Bioprinting offers virtually limitless applications and possibly resolving the issue of organ rejection due to blood transfusion reactions. This report focuses on the materials and technique for bioprinting with the aid of bioprinter alongside the use of different “bioinks” with L929 cells. Materials utilized as bioinks for this particular project were agarose-collagen blend hydrogel, as well as Pluronic F127 which served as the sacrificial mold. The biomaterials used were all thermally sensitive and were investigated to determine the optimal concentration in order to meet the time of gelation of the hydrogel with embedded cells. This report first discusses the parameters of the bioprinter that affects the printing of Pluronic F127. The agarose-collagen blend hydrogel with embedded cells at optimality, should be able to hold its form and maintain high shape fidelity (printability), and concurrently, providing a viable environment for the cells to be cultured (cell viability). The cell viability aspect is discussed based on the qualitative cell proliferation observation.